2015
DOI: 10.1038/nmeth.3357
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel delivery of large cargo into mammalian cells with light pulses

Abstract: We report a high-throughput platform for delivering large cargo into 100,000 cells in 1 min. An array of micro-cavitation bubbles explode in response to laser pulsing, forming pores in adjacent cell membranes, and immediately thereafter, pressurized flows drive slow diffusing cargo through these pores into cells. The platform delivers large cargo including bacteria, enzymes, antibodies, and nanoparticles into diverse cell types with high efficiency and cell viability. We used this platform to explore the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
170
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(174 citation statements)
references
References 34 publications
3
170
1
Order By: Relevance
“…Collectively, these distinctions between virulent strains and LVS imply that the biological relevance of our current findings for F. tularensis strains in general will ultimately require that the work be validated using virulent strains. Further, it was recently shown that the ⌬iglC mutant of F. novicida U112 was unable to replicate upon delivery into the cytosol of mammalian cells (79), in contrast to our findings after microinjection. Thus, phenotypic differences appear to exist between the different subspecies of F. tularensis that affect their intracellular survival.…”
Section: Discussioncontrasting
confidence: 99%
“…Collectively, these distinctions between virulent strains and LVS imply that the biological relevance of our current findings for F. tularensis strains in general will ultimately require that the work be validated using virulent strains. Further, it was recently shown that the ⌬iglC mutant of F. novicida U112 was unable to replicate upon delivery into the cytosol of mammalian cells (79), in contrast to our findings after microinjection. Thus, phenotypic differences appear to exist between the different subspecies of F. tularensis that affect their intracellular survival.…”
Section: Discussioncontrasting
confidence: 99%
“…Spatial control can be achieved by laser excitation of an absorbent particle or substrate. Recently, this concept was scaled up for deployment with cell monolayers 93 . Substrates arrayed with pores lined by metallic absorbers were irradiated underneath adherent cells.…”
Section: Towards Precision Membrane Disruptionmentioning
confidence: 99%
“…This work represents a shift in microfluidic design that should allow microfluidic devices to be incorporated in a wider range of commercial applications. High-Throughput Photothermal BLAST Platform for Large-Cargo Intracellular Delivery 8 While there are a number of well-established methods for delivery of small-scale cargo, such as kilobit-sized nucleic acids, reliably delivering large cargo into cells has remained elusive. Developing a method for large-cargo delivery in a high-throughput manner is an even more difficult hurdle to overcome.…”
Section: A 3d Platform For Modular Microfluidic Circuitsmentioning
confidence: 99%
“…[8][9][10] This year's honorees represent the best in research that advances translational science and technology, and we are proud to honor these researchers for their amazing work. JALA and SLAS would like to thank all the nominees as well as those who nominated them.…”
mentioning
confidence: 99%